Examination of Efficient Market Hypothesis in Indian Stock Markets and behavioural patterns of Institutional and Individual Investors in India - Jain, Shruti (2006)
Over 5 decades a lot of body of evidences have claimed that stock markets are efficient and it is not possible to beat the market consistently. In recent years, however, financial economists have increasingly questioned the efficient market theory. Market efficiency has an influence on the investment strategy of an investor If market is efficient, trying to find undervalued and overvalued stocks and trying to beating the market will be a waste. In an efficient market there will be no undervalued securities offering higher than deserved expected returns, given their risk. On the other hand if markets are not efficient, excess returns can be made by correctly picking the winners. This study examines the efficiency of Indian stock markets and shows that Indian stock markets are not completely efficient. There are existence of mispriced securities and opportunities for investors to outperform the market. As against many claims that it is not possible for any Mutual Fund to beat the market consistently, this study shows that, in India, active funds exist that have beaten the markets consistently. Behavioural finance is also important in making investment decisions in India and market participants are prone to irrationalities like herding behaviour, greed, relying too much on current information that causes market inefficiency and prices of securities to deviate from their intrinsic value. The study also outlines how investors can identify good investment opportunities.